2005
DOI: 10.1056/nejmoa044456
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Blockers to Prevent Gastroesophageal Varices in Patients with Cirrhosis

Abstract: Nonselective beta-blockers are ineffective in preventing varices in unselected patients with cirrhosis and portal hypertension and are associated with an increased number of adverse events. (ClinicalTrials.gov number, NCT00006398.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
668
6
37

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 892 publications
(723 citation statements)
references
References 33 publications
12
668
6
37
Order By: Relevance
“…Our findings support the current empirical recommendation that patients with PVT without varices need to be submitted to follow-up screening endoscopies. Indeed, the observed incidence of EVs in our study is almost identical to that found in the prospective timolol study (17) and only slightly lower than the 5%, 17%, and 28% at 1, 2, and 3 years, respectively, reported in patients with cirrhosis by Merli et al (18) Although ours was not a prospective study, in our cohort of patients the median interval time between baseline and follow-up endoscopies was 17.6 months, lower than the 2-year to 3-year interval recommended to assess variceal development in patients with compensated cirrhosis. (5) There are scarce data on the probability of variceal growth in patients with PVT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings support the current empirical recommendation that patients with PVT without varices need to be submitted to follow-up screening endoscopies. Indeed, the observed incidence of EVs in our study is almost identical to that found in the prospective timolol study (17) and only slightly lower than the 5%, 17%, and 28% at 1, 2, and 3 years, respectively, reported in patients with cirrhosis by Merli et al (18) Although ours was not a prospective study, in our cohort of patients the median interval time between baseline and follow-up endoscopies was 17.6 months, lower than the 2-year to 3-year interval recommended to assess variceal development in patients with compensated cirrhosis. (5) There are scarce data on the probability of variceal growth in patients with PVT.…”
Section: Discussionsupporting
confidence: 90%
“…Follow-up endoscopy was not performed due to follow-up time <2 years in five patients and for unknown reasons in four. Median elapsed time was 27 months (range 9-218) months, the time/endoscopy index was 11 (range 5-83) months, and the median number of endoscopies performed was two (range [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19].…”
Section: Ev Growthmentioning
confidence: 99%
“…15 HVPG Ͼ10 mmHg predicts the development of complications of HCV cirrhosis. 16 HVPG has been put forward as a test that would reflect progression during both precirrhotic and cirrhotic stages of HCV liver disease and be an end point in antiviral therapy, irrespective of antiviral response. 17 Fibrosis associated with recurrent HCV infection after liver transplantation (LT).…”
mentioning
confidence: 99%
“…In accordance to previous studies, a UGIE every 2 years is considered sufficient for patients without varices [7]. Patients with small varices develop large varices at a rate of 5-12% per year [13,19]. Decompensated cirrhosis (Child-Turcotte-Pugh B and C), alcohol etiology, or the presence of red signs at the time of baseline UGIE is associated with rapid progression from small to large varices and a more strict surveillance with UGIEs at 1-year intervals is recommended [19].…”
Section: Definitions Of Varices and Variceal Bleed Prophylaxismentioning
confidence: 59%
“…Quite often, early primary prophylaxis has been used for both groups of patients [13]. To clarify the matter, another term preprimary prophylaxis, which has been used by some investigators, was suggested.…”
Section: Definitions Of Varices and Variceal Bleed Prophylaxismentioning
confidence: 99%